Epigenetic Regulation Of Axon Regeneration and Glial Activation in Injury Responses - Wahane, Shalaka; Halawani, Dalia; Zhou, Xiang; Zou, Hongyan (Frontiers in Genetics, 2019)
Injury to the nervous system triggers a multicellular response in which epigenetic mechanisms play an important role in regulating cell type-specific transcriptional changes. Here, we summarize recent progress in characterizing neuronal intrinsic and extrinsic chromatin reconfigurations and epigenetic changes triggered by axonal injury that shape neuroplasticity and glial functions. We specifically discuss regeneration-associated transcriptional modules comprised of transcription factors and epigenetic regulators that control axon growth competence. We also review epigenetic regulation of neuroinflammation and astroglial responses that impact neural repair. These advances provide a framework for developing epigenetic strategies to maximize adaptive alterations while minimizing maladaptive stress responses in order to enhance axon regeneration and achieve functional recovery after injury.